AN INVESTIGATION OF EFL YOUNG LEARNERS’ INTEREST AND MOTIVATION IN LEARNING ENGLISH: A CASE STUDY OF MADRASAH IBTIDAIYAH STUDENTS - Hafizah, Dinda; Fithriani, Rahmah (Attadib: Journal of Elementary Education, 2023)
This present research investigated the English learning interest and motivation of EFL Madrasah Ibtidaiyah (Islamic elementary school) students. The study employs a quantitative descriptive methodology, where by data is gathered through means of observation, documentation, and questionnaires. Participants included 30 English as a Foreign Language (EFL) learners who were enrolled at Madrasah Ibtidaiyah (Islamic primary school) located in Medan, Indonesia. The questionnaire comprises a set of inquiries that have been modified to assess the overall interest of students towards speaking, reading, listening, and writing, along with inquiries pertaining to their intrinsic and extrinsic motivation. The results of questionnaires and observation notes indicate that the level of interest and motivation exhibited by EFL students towards learning the English language is notably high. Based on the distribution of scores, it can be inferred that students exhibit the highest level of interest in English listening skills, followed by reading, speaking, and lastly, writing. The primary determinant of intrinsic motivation among students is their personal inclination towards acquiring proficiency in the English language. The primary factor contributing to students' extrinsic motivation is the teacher, including her instructional methods, use of media, and recognition of outstanding academic performance. Of the two components, extrinsic motivation outweighs intrinsic motivation in terms of percentage score. The findings of this study suggest that teachers have a significant role in sustaining and/or enhancing students' interest and motivation in learning English.